THE ROLE OF INVESTIGATIVE JOURNALISM IN UNCOVERING CYBERCRIME: A CRIMINOLOGICAL AND SHARIA LAW ANALYSIS - Ashidiq, Abdul Rahman; Arifah (MEDIOVA: Journal of Islamic Media Studies, 2025)
This study aims to analyze the role of investigative journalism in uncovering cybercrime using a literature approach that integrates criminology and sharia law perspectives. The study uses a qualitative-descriptive literature study method with data collected from academic journals, books on communication theory, media ethics, cybercriminology, and Islamic law literature. The results show that investigative journalism has a strategic function as a social control that can uncover hidden cybercrime practices, encourage transparency, accountability, and policy reform. The criminology perspective provides an understanding of the dynamics of criminal behavior and its preventive function, while sharia law emphasizes the principles of justice, ethics, and victim recovery in cyber law enforcement. The integration of these two perspectives builds an ethical framework for cyber journalism that is responsible, fair, and professional. This study recommends strengthening the capacity of investigative journalists through technology and legal training and the development of regulations that accommodate positive legal aspects and sharia values to face the challenges of digital crime effectively and sustainably.